The political transformation of Gulf tribal states : elitism and the social contract in Kuwait, Bahrain and Dubai, 1918-1970s - Yanai, Shaul (Sussex Academic Press, 2014)
This study details how the reform movements and attempts to establish parliamentary institutions in the Persian Gulf states of Kuwait, Bahrain, and Dubai between the First World War and the independent era of the 1970s represented a milestone in the history of the region, creating a legacy for future generations, but was a unique transition in the Arab world. An important work to understanding the history of the Persian Gulf states, the book illustrates how, as this new political and social order evolved, ideas of national struggle and national rights penetrated Gulf societies. Gulf citizens w.
Keywords: Social change -- Persian Gulf States -- History -- 20th century.; Political culture -- Persian Gulf States -- History -- 20th century.; Tribal government -- Persian Gulf States -- History -- 20th century.; Elite (Social sciences) -- Persian Gulf States -- History -- 20th century.; Social contract -- History -- 20th century.; Persian Gulf States -- Politics and government -- 20th century.; Kuwait -- Politics and government -- 20th century.; Bahrain -- Politics and government -- 20th century.; Dubayy (United Arab Emirates : Emirate) -- Politics and government -- 20th century.; Gouvernement tribal -- États du golfe Persique -- Histoire -- 20e siècle.; Élite (Sciences sociales) -- États du golfe Persique -- Histoire -- 20e siècle.; Contrat social -- Histoire -- 20e siècle.; HISTORY -- Middle East -- General.; Elite (Social sciences); Political culture; Politics and government; Social change; Social contract; Tribal government; Bahrain; Kuwait; Persian Gulf States; United Arab Emirates -- Dubayy (Emirate); 1900-1999; History